The Effect Of Work Training, Work Environment And Work Motivation On The Work Productivity Of PT. XYZ - Nita Rahmayanti; Putri Maisara (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2023)
The purpose of this study was to determine the effect of job training and the work environment on the work productivity of PT. XZY. Quantitative data collection through questionnaires distributed to Department employees Cutting PT. XZY which is 166 is the method used in this study. The analytical tools used were data instrument testing, classical assumption testing, hypothesis testing, and multiple linear regression testing using SPSS version 25. The results of the t test in this study were job training partially having a positive and significant effect on work productivity at PT. XYZ, the work environment partially has a positive and significant effect on the work productivity of employees of PT. XYZ, work motivation partially has a positive and significant effect on the work productivity of PT. XYZ. The results of the job training f test, work environment, work motivation simultaneously affect the work productivity of employees of PT. XYZ.